Simulation of lumbar and neck angle flexion while ingress of paratransit (angkot) in Indonesia as a preliminary design study - Yukhi Mustaqim Kusuma Sya’bana; Kadek Heri Sanjaya; Muhammad Redho Kurnia; James Shippen (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2017)
This is the preliminary finding of a study to simulate lumbar and neck flexion while ingress to the paratransit. The result of simulation will determine design aspect criteria as a preliminary step before ideation and implementation design steps. Biomechanics of Bodies (BoB) is software that used to represent passenger task during paratransit ingress simulation, with skeleton model that used is height 165 cm and weight 65 kg. Environment to represent this simulation is measured Suzuki Carry SS 2013 as a private car that has been modified into a public transportation in accordance with the Indonesian government road-worthy test. Due to the low height of the entrance and the high ground clearance, lumbar and neck joint angle was a focus of this ingress simulation. The peak angle at the neck joint is 40° when 2 s skeleton nod in the door limitation ingress and lumbar flexion is 70° when 5 s skeleton is walking while bend over that will increase the load on that area. Based on biomechanical simulation approach, we may suggest the dimension of public transportation design framework developments, especially paratransit.